The Linguopragmatic Characteristics of Air Traffic Control Discourse (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the linguopragmatic characteristics of Air Traffic Control (ATC) discourse, focusing on the interactional mechanisms that ensure clarity, precision, and safety in aviation communication. The study analyzes the pragmatic functions of standardized phraseology, the role of illocutionary force in directive speech acts, and the importance of context in interpreting instructions between pilots and controllers. Special attention is given to communicative economy, redundancy, repetition, and confirmation strategies as essential tools for preventing ambiguity and minimizing risks in high-stakes environments. Through illustrative examples from real ATC exchanges, the article highlights how linguistic form, pragmatic intent, and situational constraints collectively shape effective communication. The findings demonstrate that ATC discourse represents a unique type of institutional communication where linguistic constraints directly contribute to operational safety and efficient air traffic management.